2013
DOI: 10.1021/la400756z
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Mediated Short-Range Attraction Drives Aggregation of Charged Monolayer-Protected Gold Nanoparticles

Abstract: Monolayer-protected gold nanoparticles (AuNPs) are a promising new class of nanomaterials with applications in drug delivery, self-assembly, and biosensing. The versatility of the AuNP platform is conferred by the properties of the protecting monolayer which can be engineered to tune the surface functionality of the nanoparticles. However, many applications are hampered by AuNP aggregation, which can inhibit functionality or induce particles to precipitate out of solution, even for water-soluble AuNPs. It is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 65 publications
3
49
0
Order By: Relevance
“…At this separation, the long ligands mostly bend out of the inter-AuNPs space so that the hydrophobic hydrocarbon chains are exposed toward one another, in agreement with the observations in Ref. 19. The hydrophobic interaction between the two AuNPs gives rise to the PMF well shown in Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…At this separation, the long ligands mostly bend out of the inter-AuNPs space so that the hydrophobic hydrocarbon chains are exposed toward one another, in agreement with the observations in Ref. 19. The hydrophobic interaction between the two AuNPs gives rise to the PMF well shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…Depending on the intended medical application, a high propensity to aggregate may be a desirable property, and may even be tuned by modifying the ligand. 19 On the μm-scale, numerous studies performed on charged colloids interacting in electrolyte solutions have shown that they display attraction when equally charged. 20-30 …”
Section: Introductionmentioning
confidence: 99%
“…Although it might be difficult to realize such effective interactions for micron-sized colloidal particles, it should be possible for nanoscale particles. As an example, potentials of mean force observed in simulations of ligand-coated, charge-stabilized gold nanoparticles display a similar qualitative form [19]. Moreover, in future work, a similar relative entropy approach could be used to limit the range of the attraction for application to colloids as well as to explore the range of parameters that can be employed in the target simulation to successfully make pores, particularly with respect to pore size and pore density.…”
mentioning
confidence: 90%
“…66 At the level of the pair free energy change between two such particles along a radial coordinate, they found from van der Waals, electrostatic, phobic and entropy contributions that a wide attractive basin followed by a repulsive hump can be realized. 66 At the level of the pair free energy change between two such particles along a radial coordinate, they found from van der Waals, electrostatic, phobic and entropy contributions that a wide attractive basin followed by a repulsive hump can be realized.…”
Section: Optimized Potentialsmentioning
confidence: 99%